Optical glass, glass preform, optical element, and optical instrument
Patent Information
- Application Number
- CN202611386860.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-27
AI Technical Summary
[0017]本发明的有益效果是:通过合理的组分设计,本发明光学玻璃在具有负向相对部分色散偏离值的同时,还具有较高的硬度。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to an optical glass, and more particularly to an optical glass having a negative relative partial dispersion deviation and high hardness, as well as glass preforms, optical elements and optical instruments made therefrom. Background Technology
[0002] In recent years, with the rapid development of technologies such as surveillance and security, and vehicle imaging, the demand for optical glass used in these instruments has continued to increase. To improve the design freedom of optical systems, a variety of optical glass properties are desired. Therefore, optical glass with the ability to eliminate or minimize residual chromatic aberration in the secondary spectrum has attracted much attention, especially those with low negative relative partial dispersion deviation (ΔP). g,F Optical glass. Among optical glasses used to manufacture optical components, especially those capable of chromatic aberration correction, possessing a negative relative partial dispersion deviation value and a refractive index (n...)... d The Abbe number (ν) ranges from 1.590 to 1.660. d The demand for optical glass with a thickness of 55.5 to 62.5 is increasing. At the same time, fields such as automotive imaging and security monitoring have high requirements for the hardness of the optical glass used in them. High hardness of optical glass is beneficial to resisting the wear and tear and impact of sand and gravel during vehicle operation, which can extend its service life. Summary of the Invention
[0003] The technical problem to be solved by the present invention is to provide an optical glass with a negative relative partial dispersion deviation value and high hardness, as well as glass preforms, optical elements and optical instruments made therefrom.
[0004] The technical solution adopted by this invention to solve the technical problem is:
[0005] (1) Optical glass, the composition of which is expressed as a weight percentage, contains: SiO2: 18%~33%; B2O3: 18%~33%; SrO: 3%~15%; BaO: 13%~26%; La2O3: 9%~23%; ZrO2: 0.1%~9%; Al2O3: 0.1%~9%, of which SrO / ZrO2 is 1.00~8.00.
[0006] (2) The optical glass according to (1) further comprises, by weight percentage: MgO: 0-4.5%; and / or CaO: 0-4.5%; and / or ZnO: 0-4.5%; and / or Gd2O3: 0-4.5%; and / or Y2O3: 0-4.5%; and / or Yb2O3: 0-4.5%; and / or AlF3: 0-6%; and / or Li2O: 0-4.5%; and / or Na2O: 0-4.5%; and / or K2O: 0-4.5%; and / or Nb2O5: 0-3%; and / or TiO2: 0-3%; and / or WO3: 0-3%; and / or Ta2O5: 0-3%; and / or P2O5: 0-3%; and / or clarifying agent: 0-1%, wherein the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.
[0007] (3) Optical glass containing SiO2, B2O3, SrO, BaO, La2O3, ZrO2 and Al2O3, the composition of which is expressed as a weight percentage, wherein the SrO / ZrO2 ratio is 1.00 to 8.00, and the refractive index n of the optical glass is... d The Abbe number ν ranges from 1.590 to 1.660. d Its strength ranges from 55.5 to 62.5, and its Knoop hardness is 520 × 10⁻⁶. 7 Above Pa, the relative partial dispersion deviation ΔP g,F It is below -0.0010.
[0008] (4) The optical glass according to (3) comprises, by weight percentage: SiO2: 18%–33%; and / or B2O3: 18%–33%; and / or SrO: 3%–15%; and / or BaO: 13%–26%; and / or La2O3: 9%–23%; and / or ZrO2: 0.1%–9%; and / or Al2O3: 0.1%–9%; and / or MgO: 0–4.5%; and / or CaO: 0–4.5%; and / or ZnO: 0–4.5%; and / or Gd2O3: 0–4.5%. ; and / or Y2O3: 0-4.5%; and / or Yb2O3: 0-4.5%; and / or AlF3: 0-6%; and / or Li2O: 0-4.5%; and / or Na2O: 0-4.5%; and / or K2O: 0-4.5%; and / or Nb2O5: 0-3%; and / or TiO2: 0-3%; and / or WO3: 0-3%; and / or Ta2O5: 0-3%; and / or P2O5: 0-3%; and / or clarifying agent: 0-1%, wherein the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.
[0009] (5) The optical glass according to any one of (1) to (4), wherein the composition is expressed as a weight percentage, wherein: SrO / ZrO2 is 1.40 to 6.00, preferably SrO / ZrO2 is 1.70 to 3.00; and / or (La2O3+SrO) / SiO2 is 0.50 to 2.00, preferably (La2O3+SrO) / SiO2 is 0.60 to 1.60, more preferably (La2O3+SrO) / SiO2 is 0.75 to 1.20; and / or 2×AlF3 / (SrO-ZrO2-Gd2O3-Y2O3-ZnO-Li2O-Na2O) The content of 2×AlF3 / (SrO-ZrO2-Gd2O3-Y2O3-ZnO-Li2O-Na2O-K2O) is 0.02 to 7.00, preferably 0.10 to 3.00, more preferably 0.20 to 1.00; and / or 0.02 to 3.00 for 5×AlF3 / La2O3, preferably 0.05 to 2.00, more preferably 0.10 to 1.00.
[0010] (6) The optical glass according to any one of (1) to (4), wherein the composition is expressed as a weight percentage, wherein: (La2O3+Gd2O3+Y2O3+CaO) / SrO is 0.80 to 4.50, preferably (La2O3+Gd2O3+Y2O3+CaO) / SrO is 1.20 to 3.50, more preferably (La2O3+Gd2O3+Y2O3+CaO) / SrO is 1.60 to 2.50; and / or (TiO2+Nb2O5+WO3+Ta2O5) / SrO is 0.80 or less, preferably (TiO2+Nb2O5+WO3+Ta2O5) / SrO is 0.50 or less, more preferably (TiO2+Nb2O5+WO3+Ta2O5) / SrO is 0.50 or less, more preferably (TiO2+Nb2O5+WO3+Ta2O5) / SrO is 0.50 or less, more preferably (TiO2+Nb2O5+WO3+Ta2O5+WO3+Ta2O5) / SrO is 0.80 or less, more preferably (TiO2+Nb2O5+WO3+Ta ...Ta2O5+WO3+Ta2O5+Ta2O5+WO3+Ta2O5+Ta2O5+Ta The ratio of (TiO2+Nb2O5+WO3+Ta2O5) / SrO is 0.30 or less, more preferably (TiO2+Nb2O5+WO3+Ta2O5) / SrO is 0.10 or less; and / or the ratio of (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) / SrO is 1.00 or less, preferably (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) / SrO is 0.70 or less, more preferably (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) / SrO is 0.70 or less, more preferably (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) / SrO is 0.30 or less. The ratio of (Li₂O₅) / SrO is 0.40 or less, more preferably (Li₂O+Na₂O+K₂O+Gd₂O₃+Y₂O₃+ZnO+CaO+MgO+TiO₂+Nb₂O₅) / SrO is 0.10 or less; and / or (La₂O₃+SrO+BaO) / B₂O₃ is 1.00 to 2.60, preferably (La₂O₃+SrO+BaO) / B₂O₃ is 1.30 to 2.30, more preferably (La₂O₃+SrO+BaO) / B₂O₃ is 1.50 to 2.00; and / or (La₂O₃+Gd₂O₃+Y₂O₃+Yb₂O₃+ZnO) / BaO is 0.40 to 2.00, more preferably (La₂O₃+Gd₂O₃+Y₂O₃+ZnO+CaO+MgO+TiO₂+Nb₂O₅) / Sr ...10 to 0.10; The ratio of (La₂O₃+Gd₂O₃+Y₂O₃+Yb₂O₃+ZnO) / BaO is 0.50–1.50, more preferably (La₂O₃+Gd₂O₃+Y₂O₃+Yb₂O₃+ZnO) / BaO is 0.60–1.20; and / or (SiO₂+BaO+CaO+MgO+ZrO₂+Gd₂O₃+Y₂O₃) / B₂O₃ is 1.00–3.20, more preferably (SiO₂+BaO+CaO+MgO+ZrO₂+Gd₂O₃+Y₂O₃) / B₂O₃ is 1.30–2.80, more preferably (SiO₂+BaO+CaO+MgO+ZrO₂+Gd₂O₃+Y₂O₃) / B₂O₃ is 1.60–2.20.
[0011] (7) The optical glass according to any one of (1) to (4), wherein the composition is expressed as a weight percentage, wherein: BaO / (ZrO2+Al2O3) is 1.00 to 8.00, preferably BaO / (ZrO2+Al2O3) is 1.50 to 5.50, more preferably BaO / (ZrO2+Al2O3) is 2.30 to 3.50; and / or (Li2O+Na2O+K2O+MgO+CaO) The ratio of (Li₂O+Na₂O+K₂O+MgO+CaO+ZnO) / (ZrO₂+Al₂O₃) is 1.00 or less, preferably 0.70 or less, more preferably 0.40 or less, and even more preferably 0.40 or less. The ratio of (O+CaO+ZnO) / (ZrO2+Al2O3) is 0.01 to 0.15; and / or the ratio of (Gd2O3+Y2O3) / ZrO2 is 1.00 or less, preferably (Gd2O3+Y2O3) / ZrO2 is 0.70 or less, more preferably (Gd2O3+Y2O3) / ZrO2 is 0.50 or less, and even more preferably (Gd2O3+Y2O3) / ZrO2 is 0.20 or less; and / Alternatively, the ratio of AlF3 / (Al2O3-Gd2O3-Y2O3-K2O-Na2O-P2O5) may be 0.01 to 6.00, preferably 0.05 to 2.50, and more preferably 0.10 to 1.00.
[0012] (8) The optical glass according to any one of (1) to (4), wherein the composition is expressed as a weight percentage, wherein: SiO2: 21% to 30%, preferably SiO2: 23% to 27%; and / or B2O3: 21% to 30%, preferably B2O3: 23% to 27%; and / or SrO: 5% to 12%, preferably SrO: 6% to 10.5%; and / or BaO: 15% to 24%, preferably BaO: 17% to 22%; and / or La2O3: 11% to 19.5%, preferably La2O3: 13% to 18%; and / or ZrO2: 1% to 7%, preferably ZrO2: 1% to 7%. O2: 2%–5.5%; and / or Al2O3: 1%–7%, preferably Al2O3: 2.5%–6%; and / or MgO: 0%–3%, preferably MgO: 0%–1%, more preferably MgO-free; and / or CaO: 0%–3%, preferably CaO: 0%–1%, more preferably CaO-free; and / or ZnO: 0%–2%, preferably ZnO: 0%–0.5%, more preferably ZnO-free; and / or Gd2O3: 0%–3%, preferably Gd2O3: 0%–0.5%, more preferably Gd2O3-free; and / or Y2O3: 0%–3%, preferably Y2O3: 0%–0.5%. %, preferably free of Y2O3; and / or Yb2O3: 0-3%, preferably Yb2O3: 0-1%, more preferably free of Yb2O3; and / or AlF3: 0.1%-4.5%, preferably AlF3: 0.5%-3%; and / or Li2O: 0-3%, preferably Li2O: 0-1%; and / or Na2O: 0-3%, preferably Na2O: 0-1%, more preferably free of Na2O; and / or K2O: 0-3%, preferably K2O: 0-1%, more preferably free of K2O; and / or Nb2O5: 0-2%, preferably Nb2O5: 0-1%, more preferably free of Nb2O. The mixture contains no Nb2O5; and / or TiO2: 0-2%, preferably TiO2: 0-1%, more preferably no TiO2; and / or WO3: 0-2%, preferably WO3: 0-1%, more preferably no WO3; and / or Ta2O5: 0-2%, preferably Ta2O5: 0-1%, more preferably no Ta2O5; and / or P2O5: 0-2%, preferably P2O5: 0-1%, more preferably no P2O5; and / or clarifying agent: 0-0.5%, preferably clarifying agent: 0-0.2%, wherein the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.
[0013] (9) The optical glass according to any one of (1) to (4), wherein the refractive index n of the optical glass is d The Knoop hardness is 1.590–1.660, preferably 1.600–1.650, more preferably 1.610–1.640; and / or the Knoop hardness is 520 × 10⁻⁶. 7 Pa or higher, preferably 540 × 10 Pa7 Pa or higher, more preferably 550 × 10 Pa 7 Pa or above; and / or relative partial dispersion deviation ΔP g,F The value is -0.0010 or less, preferably -0.0020 or less, more preferably -0.0035 or less; and / or the Abbe number ν d The coefficient of thermal expansion is 55.5–62.5, preferably 56.0–61.0, more preferably 57.0–60.0; and / or the coefficient of thermal expansion α. 100℃ / 300℃ 90×10 -7 / K or less, preferably 80×10 -7 / K or less, preferably 75×10 -7 / K or below; and / or 400nm light transmittance τ 400nm The purity is 98.0% or higher, preferably 99.0% or higher, more preferably 99.5% or higher; and / or the water resistance stability is Class 2 or higher, preferably Class 1; and / or the weather resistance is Class 2 or higher, preferably Class 1; and / or the density is 3.70 g / cm³. 3 The preferred value is 3.60 g / cm³. 3 The following is a preferred value: 3.50 g / cm³ 3 The following is a further preferred value: 3.45 g / cm³ 3 The following are also considered: a transition temperature of 610°C to 680°C, preferably 620°C to 665°C, more preferably 630°C to 655°C; a wear degree of 105 to 139, preferably 110 to 134, more preferably 116 to 128; a Young's modulus of 82.0 GPa or higher, preferably 85.0 GPa or higher, more preferably 87.0 GPa or higher; and / or a bubble degree of A grade or higher, preferably A0 grade or higher, more preferably A. 00 Grade; and / or stripe density of grade C or above, preferably grade B or above.
[0014] (10) Glass preforms, made of any one of the optical glass described in (1) to (9).
[0015] (11) An optical element made of any one of the optical glass described in (1) to (9), or made of the glass preform described in (10).
[0016] (12) An optical instrument containing optical glass as described in any one of (1) to (9), and / or containing optical elements as described in (11).
[0017] The beneficial effects of the present invention are: through reasonable component design, the optical glass of the present invention has high hardness while having a negative relative partial dispersion deviation value. Detailed Implementation
[0018] The embodiments of the optical glass of the present invention will now be described in detail. However, the present invention is not limited to the embodiments described below, and appropriate modifications can be made to implement it within the scope of the purpose of the present invention. Furthermore, regarding repeated descriptions, although there are appropriate omissions, this will not limit the spirit of the invention. In the following text, the optical glass of the present invention may be simply referred to as glass.
[0019] Optical Glass
[0020] The composition range of each component in the optical glass of the present invention is described below. In the present invention, unless otherwise specified, the content of each component, the total content, the total content, etc. are all expressed as weight percentage (wt%), that is, the weight percentage of the content of each component, the total content, the total content relative to the total amount of glass material converted into oxides and / or fluorides.
[0021] Unless otherwise specified in the specific context, the numerical ranges listed in this invention include upper and lower limits, and "above" and "below" include endpoint values and all integers and fractions included in the range, but are not limited to the specific values listed when the range is defined. The term "and / or" as used herein is inclusive; for example, "A and / or B" means only A, or only B, or both A and B.
[0022] <Essential and Optional Components>
[0023] SiO2 is the framework of the glass of this invention. It can increase the viscosity of the molten glass, improve the glass's resistance to devitrification and chemical stability, and reduce the glass's abrasion resistance. However, if its content is too high, the difficulty of melting the glass increases, the transition temperature rises, and the refractive index decreases. Therefore, the SiO2 content in this invention is 18% to 33%, preferably 21% to 30%, and more preferably 23% to 27%. In some embodiments, the SiO2 content can be 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0024] B2O3 is a component of the glass network forging system, which can improve the stability, melt flow properties, and resistance to crystallization of glass. However, if the B2O3 content is too high, the chemical stability and mechanical properties of the glass will decrease, and the devitrification resistance will decline. Therefore, the B2O3 content in this invention is 18% to 33%, preferably 21% to 30%, and more preferably 23% to 27%. In some embodiments, the B2O3 content can be 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0025] MgO can adjust the refractive index and melt flow properties of glass, but if the MgO content is too high, the glass's devitrification resistance and stability will decrease. Therefore, the MgO content is 0-4.5%, preferably 0-3%, and more preferably 0-1%. In some embodiments, it is further preferred that no MgO is present. In some embodiments, the MgO content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0026] CaO can improve the devitrification resistance and chemical stability of glass; however, excessive CaO content reduces the glass's resistance to crystallization. Therefore, the CaO content is 0–4.5%, preferably 0–3%, and more preferably 0–1%. In some embodiments, it is further preferred that the glass contains no CaO. In some embodiments, the CaO content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, etc., as well as all ranges and sub-ranges between these values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0027] SrO can be used to adjust the refractive index, Abbe number, and ΔP of glass. g,F The SrO content improves the melt flow properties and weather resistance of the glass, and increases its light transmittance; however, if the content is too high, the glass's devitrification resistance decreases. Therefore, the SrO content is 3% to 15%, preferably 5% to 12%, and more preferably 6% to 10.5%. In some embodiments, the SrO content can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0028] BaO can improve the devitrification resistance and hardness of glass, and reduce the temperature coefficient of refractive index and the coefficient of thermal expansion of glass. However, if its content is too high, the chemical stability and resistance to crystallization of the glass will decrease. Therefore, the BaO content in this invention is 13% to 26%, preferably 15% to 24%, and more preferably 17% to 22%. In some embodiments, the BaO content can be 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0029] ZnO can improve the melting properties of glass and lower its transition temperature, but when its content is too high, the glass's devitrification resistance decreases, and it is detrimental to maintaining the glass's anti-crystallization stability and high transmittance. Therefore, the ZnO content in this invention is 0-4.5%, preferably 0-2%, and more preferably 0-0.5%. In some embodiments, it is further preferred that the glass does not contain ZnO. In some embodiments, the ZnO content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0030] La2O3 can increase the refractive index of glass and regulate dispersion, improve the thermal and chemical stability of glass, and reduce the high-temperature viscosity of glass. However, if its content is too high, the anti-crystallization performance of glass will decrease and the transition temperature will increase. Therefore, the content of La2O3 in this invention is 9% to 23%, preferably 11% to 19.5%, and more preferably 13% to 18%. In some embodiments, the content of La2O3 can be 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0031] In some embodiments, by controlling the ratio of the total content of La2O3 and SrO (La2O3+SrO) to the content of SiO2 (La2O3+SrO) / SiO2 within the range of 0.50 to 2.00, the Young's modulus of the glass can be improved while preventing the glass's ΔP from deteriorating. g,FThe value increases. Therefore, it is preferable that (La2O3+SrO) / SiO2 is 0.50 to 2.00, more preferably (La2O3+SrO) / SiO2 is 0.60 to 1.60, and even more preferably (La2O3+SrO) / SiO2 is 0.75 to 1.20. In some implementations, the value of (La2O3+SrO) / SiO2 can be 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, or 1. 23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0032] In some embodiments, by controlling the ratio (La2O3+SrO+BaO) / B2O3 between the total content of La2O3, SrO, and BaO (La2O3+SrO+BaO) and the content of B2O3 (La2O3+SrO+BaO) / B2O3 in the range of 1.00 to 2.60, the glass can achieve the desired transition temperature more easily while improving its resistance to crystallization. Therefore, it is preferable that (La2O3+SrO+BaO) / B2O3 is 1.00 to 2.60, more preferably (La2O3+SrO+BaO) / B2O3 is 1.30 to 2.30, and even more preferably (La2O3+SrO+BaO) / B2O3 is 1.50 to 2.00. In some implementations, the value of (La2O3+SrO+BaO) / B2O3 can be 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.03, 2.05, 2.07, 2.10, 2.13, 2.15, 2.17, 2.20, 2.23, 2.25, 2.27, 2.30, 2.33, 2.35, 2.37, 2.40, 2.43, 2.45, 2.47, 2.50, 2.53, 2.55, 2.57, 2.60, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0033] Gd₂O₃ can increase the refractive index of glass and improve its resistance to crystallization. However, if its content is too high, the glass's resistance to devitrification and chemical stability will deteriorate, and ΔP will decrease. g,FThe value increases. Therefore, the content of Gd2O3 in this invention is 0-4.5%, preferably 0-3%, more preferably 0-0.5%. In some embodiments, it is further preferred that Gd2O3 is not present. In some embodiments, the content of Gd2O3 can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0034] Y₂O₃ can improve the refractive index and devitrification resistance of glass, and adjust the Young's modulus of glass. However, if its content is too high, the chemical stability and weather resistance of the glass will deteriorate. Therefore, the Y₂O₃ content in this invention is 0-4.5%, preferably 0-3%, and more preferably 0-0.5%. In some embodiments, it is further preferred that it does not contain Y₂O₃. In some embodiments, the Y₂O₃ content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0035] In some embodiments, the ratio of the total content of La2O3, Gd2O3, Y2O3, and CaO (La2O3+Gd2O3+Y2O3+CaO) to the content of SrO (La2O3+Gd2O3+Y2O3+CaO) / SrO is controlled within the range of 0.80 to 4.50. This can improve the streaking of the glass while optimizing its abrasion resistance. Therefore, it is preferable that (La2O3+Gd2O3+Y2O3+CaO) / SrO is 0.80 to 4.50, more preferably (La2O3+Gd2O3+Y2O3+CaO) / SrO is 1.20 to 3.50, and even more preferably (La2O3+Gd2O3+Y2O3+CaO) / SrO is 1.60 to 2.50. In some implementations, the value of (La₂O₃+Gd₂O₃+Y₂O₃+CaO) / SrO can be 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, or 1.2. 7, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1. 97, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, 2.55, 2.60, 2.65, 2.70, 2.75, 2.80, 2.85, 2.90, 2.95, 3.00, 3.05, 3.10, 3.15, 3.20, 3.25, 3.30 3.35, 3.40, 3.45, 3.50, 3.55, 3.60, 3.65, 3.70, 3.75, 3.80, 3.85, 3.90, 3.95, 4.00, 4.05, 4.10, 4.15, 4.20, 4.25, 4.30, 4.35, 4.40, 4.45, 4.50, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0036] Yb₂O₃ is a high-refractive-index, low-dispersion component that can improve the refractive index of glass. However, if its content exceeds 4.5%, the glass's resistance to crystallization decreases. Therefore, the content of Yb₂O₃ is 0–4.5%, preferably 0–3%, and more preferably 0–1%. In some embodiments, it is further preferred that the glass does not contain Yb₂O₃. In some embodiments, the content of Yb₂O₃ can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0037] In some embodiments, by controlling the ratio between the total content of La2O3, Gd2O3, Y2O3, Yb2O3, and ZnO (La2O3+Gd2O3+Y2O3+Yb2O3+ZnO) and the content of BaO (La2O3+Gd2O3+Y2O3+Yb2O3+ZnO) / BaO within the range of 0.40 to 2.00, the light transmittance of the glass can be improved while optimizing the bubble content of the glass. Therefore, the preferred ratio of (La2O3+Gd2O3+Y2O3+Yb2O3+ZnO) / BaO is 0.40 to 2.00, more preferably (La2O3+Gd2O3+Y2O3+Yb2O3+ZnO) / BaO is 0.50 to 1.50, and even more preferably (La2O3+Gd2O3+Y2O3+Yb2O3+ZnO) / BaO is 0.60 to 1.20. In some implementations, the value of (La₂O₃+Gd₂O₃+Y₂O₃+Yb₂O₃+ZnO) / BaO can be 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, or 1.13. The values are 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0038] ZrO2 can improve the refractive index and devitrification resistance of glass, as well as its chemical stability and mechanical properties. However, if its content is too high, the melting difficulty of the glass increases, making it prone to inclusions and a decrease in light transmittance, while also reducing the glass's resistance to crystallization. Therefore, in this invention, the ZrO2 content is 0.1% to 9%, preferably 1% to 7%, and more preferably 2% to 5.5%. In some embodiments, the ZrO2 content can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, 5.3%, 5.5%, 5.7%, 6%, 6.3%, 6.5%, 6.7%, 7%, 7.5%, 8%, 8.5%, 9%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0039] In some embodiments, controlling the SrO / ZrO2 ratio (SrO / ZrO2) within the range of 1.00 to 8.00 can improve the hardness of the glass while reducing its ΔP. g,FTherefore, the preferred SrO / ZrO2 ratio is 1.00 to 8.00, more preferably 1.40 to 6.00, and even more preferably 1.70 to 3.00. In some implementations, the SrO / ZrO2 value can be 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4... 50, 4.60, 4.70, 4.80, 4.90, 5.00, 5.10, 5.20, 5.30, 5.40, 5.50, 5.60, 5.70, 5.80, 5.90, 6.00, 6.10, 6.20, 6.30, 6.40, 6.50, 6.60, 6.70, 6.80, 6.90, 7.00, 7.10, 7.20, 7.30, 7.40, 7.50, 7.60, 7.70, 7.80, 7.90, 8.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0040] In some embodiments, the ratio between the total content of SiO2, BaO, CaO, MgO, ZrO2, Gd2O3, and Y2O3 (SiO2+BaO+CaO+MgO+ZrO2+Gd2O3+Y2O3) and the content of B2O3 (SiO2+BaO+CaO+MgO+ZrO2+Gd2O3+Y2O3) / B2O3 is controlled within the range of 1.00 to 3.20, which can optimize the bubble content of the glass while reducing its density. Therefore, the preferred ratio of (SiO2+BaO+CaO+MgO+ZrO2+Gd2O3+Y2O3) / B2O3 is 1.00 to 3.20, more preferably (SiO2+BaO+CaO+MgO+ZrO2+Gd2O3+Y2O3) / B2O3 is 1.30 to 2.80, and even more preferably (SiO2+BaO+CaO+MgO+ZrO2+Gd2O3+Y2O3) / B2O3 is 1.60 to 2.20. In some implementations, the value of (SiO2+BaO+CaO+MgO+ZrO2+Gd2O3+Y2O3) / B2O3 can be 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1 0.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00 2.03, 2.05, 2.07, 2.10, 2.13, 2.15, 2.17, 2.20, 2.23, 2.25, 2.27, 2.30, 2.33, 2.35, 2.37, 2.40, 2.43, 2.45, 2.47, 2.50, 2.53, 2.55, 2.57, 2.60, 2.63, 2.65 The values are 2.67, 2.70, 2.73, 2.75, 2.77, 2.80, 2.83, 2.85, 2.87, 2.90, 2.93, 2.95, 2.97, 3.00, 3.03, 3.05, 3.07, 3.10, 3.13, 3.15, 3.17, 3.20, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0041] In some embodiments, the ratio of the total content of Gd2O3 and Y2O3 (Gd2O3+Y2O3) to the content of ZrO2 (Gd2O3+Y2O3) / ZrO2 is controlled to be below 1.00 to prevent a decrease in the chemical stability (such as water resistance, acid resistance, etc.) and devitrification resistance of the glass. Therefore, it is preferable that (Gd2O3+Y2O3) / ZrO2 is below 1.00, more preferably (Gd2O3+Y2O3) / ZrO2 is below 0.70, further preferably (Gd2O3+Y2O3) / ZrO2 is below 0.50, and even more preferably (Gd2O3+Y2O3) / ZrO2 is below 0.20. In some implementations, the value of (Gd₂O₃+Y₂O₃) / ZrO₂ can be 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, or 0. 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0042] Al2O3 can reduce the thermal expansion coefficient and ΔP of glass. g,F The Al2O3 content is high, which improves the thermal stability of the glass; however, excessive Al2O3 content will lead to an increase in the glass transition temperature and a decrease in the glass's meltability. Therefore, the Al2O3 content in this invention is 0.1% to 9%, preferably 1% to 7%, and more preferably 2.5% to 6%. In some embodiments, the Al2O3 content can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, 5.3%, 5.5%, 5.7%, 6%, 6.3%, 6.5%, 6.7%, 7%, 7.5%, 8%, 8.5%, 9%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0043] In some embodiments, the ratio of BaO content to the total content of ZrO2 and Al2O3 (ZrO2+Al2O3), BaO / (ZrO2+Al2O3), is controlled within the range of 1.00 to 8.00. This can reduce the coefficient of thermal expansion of the glass while improving its light transmittance. Therefore, a BaO / (ZrO2+Al2O3) ratio of 1.00 to 8.00 is preferred, a BaO / (ZrO2+Al2O3) ratio of 1.50 to 5.50 is more preferred, and a BaO / (ZrO2+Al2O3) ratio of 2.30 to 3.50 is even more preferred. In some implementations, the value of BaO / (ZrO2+Al2O3) can be 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, or 4. 40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, 5.10, 5.20, 5.30, 5.40, 5.50, 5.60, 5.70, 5.80, 5.90, 6.00, 6.10, 6.20, 6.30, 6.40, 6.50, 6.60, 6.70, 6.80, 6.90, 7.00, 7.10, 7.20, 7.30, 7.40, 7.50, 7.60, 7.70, 7.80, 7.90, 8.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0044] Li₂O can lower the glass transition temperature, adjust the high-temperature viscosity of glass, and improve the melting properties of glass. However, high Li₂O content is detrimental to the chemical stability and cost economy of glass raw materials, and can also lead to excessively low refractive index of glass. Therefore, the Li₂O content in this invention is 0–4.5%, preferably 0–3%, and more preferably 0–1%. In some embodiments, the Li₂O content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0045] Na₂O can improve the melting and transition temperature of glass, but if its content is too high, the coefficient of thermal expansion of the glass increases and its chemical stability decreases. Therefore, the Na₂O content is 0–4.5%, preferably 0–3%, and more preferably 0–1%. In some embodiments, it is further preferred that Na₂O is not present. In some embodiments, the Na₂O content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0046] K₂O improves the thermal stability and melt permeability of glass, but if its content is too high, the glass's resistance to devitrification and chemical stability deteriorates. Therefore, the K₂O content in this invention is 0–4.5%, preferably 0–3%, and more preferably 0–1%. In some embodiments, it is further preferred that no K₂O is present. In some embodiments, the K₂O content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0047] In some embodiments, by controlling the ratio (Li2O+Na2O+K2O+MgO+CaO+ZnO) / (ZrO2+Al2O3) between the total content of Li2O, Na2O, K2O, MgO, CaO, and ZnO (Li2O+Na2O+K2O+MgO+CaO+ZnO) and the total content of ZrO2 and Al2O3 (ZrO2+Al2O3) to below 1.00, the degree of bubble formation in the glass can be optimized while reducing the coefficient of thermal expansion. Therefore, it is preferable that (Li2O+Na2O+K2O+MgO+CaO+ZnO) / (ZrO2+Al2O3) is 1.00 or less, more preferably (Li2O+Na2O+K2O+MgO+CaO+ZnO) / (ZrO2+Al2O3) is 0.70 or less, even more preferably (Li2O+Na2O+K2O+MgO+CaO+ZnO) / (ZrO2+Al2O3) is 0.40 or less, and even more preferably (Li2O+Na2O+K2O+MgO+CaO+ZnO) / (ZrO2+Al2O3) is 0.01 to 0.15. In some implementations, the value of (Li₂O+Na₂O+K₂O+MgO+CaO+ZnO) / (ZrO₂+Al₂O₃) can be 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, or 0.33. The values are 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0048] TiO2 can improve the refractive index and dispersion of glass, and enhance its thermal stability. However, if its content is too high, the light transmittance and resistance to crystallization of the glass will decrease, and ΔP will also decrease. g,FThe value increases. Therefore, the TiO2 content in this invention is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that TiO2 is not present. In some embodiments, the TiO2 content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0049] Ta₂O₅ can improve the refractive index and anti-crystallization properties of glass, but if its content is too high, the glass's meltability deteriorates. Compared with other components, Ta₂O₅ is expensive, and from a practical and cost-effective perspective, its usage should be minimized. Therefore, the Ta₂O₅ content in this invention is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that Ta₂O₅ is not present. In some embodiments, the Ta₂O₅ content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0050] Nb₂O₅ can adjust the refractive index and dispersion of glass, improving its thermal stability and devitrification resistance. However, if its content is too high, the light transmittance and anti-crystallization properties of the glass will decrease. Therefore, the Nb₂O₅ content is 0–3%, preferably 0–2%, and more preferably 0–1%. In some embodiments, it is further preferred that the glass does not contain Nb₂O₅. In some embodiments, the Nb₂O₅ content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0051] In some embodiments, by controlling the ratio between the total content of Li2O, Na2O, K2O, Gd2O3, Y2O3, ZnO, CaO, MgO, TiO2, and Nb2O5 (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) and the content of SrO (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) / SrO below 1.00, the density of the glass can be reduced while preventing the glass's weather resistance from deteriorating. Therefore, it is preferable that (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) / SrO is 1.00 or less, more preferably (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) / SrO is 0.70 or less, even more preferably (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) / SrO is 0.40 or less, and even more preferably (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) / SrO is 0.10 or less. In some implementations, the value of (Li₂O+Na₂O+K₂O+Gd₂O₃+Y₂O₃+ZnO+CaO+MgO+TiO₂+Nb₂O₅) / SrO can be 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, or 0.3. 0, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0052] WO3 can improve the refractive index and mechanical strength of glass, lower the glass transition temperature, and improve the glass's resistance to crystallization. However, if its content is too high, the glass's resistance to devitrification and light transmittance will decrease. Therefore, the WO3 content in this invention is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that the glass does not contain WO3. In some embodiments, the WO3 content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0053] In some embodiments, the ratio of the total content of TiO2, Nb2O5, WO3, and Ta2O5 (TiO2+Nb2O5+WO3+Ta2O5) to the content of SrO (TiO2+Nb2O5+WO3+Ta2O5) / SrO is controlled below 0.80 to prevent a decrease in the chemical stability (such as water resistance, acid resistance, etc.) and devitrification resistance of the glass. Therefore, it is preferable that (TiO2+Nb2O5+WO3+Ta2O5) / SrO is below 0.80, more preferably (TiO2+Nb2O5+WO3+Ta2O5) / SrO is below 0.50, further preferably (TiO2+Nb2O5+WO3+Ta2O5) / SrO is below 0.30, and even more preferably (TiO2+Nb2O5+WO3+Ta2O5) / SrO is below 0.10. In some implementations, the value of (TiO2+Nb2O5+WO3+Ta2O5) / SrO can be 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0054] P2O5 can appropriately improve the devitrification resistance of glass, but if its content is too high, the chemical stability and anti-crystallization properties of the glass will decrease. Therefore, the P2O5 content is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that P2O5 is not present. In some embodiments, the P2O5 content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0055] AlF3 can improve the devitrification resistance and light transmittance of glass, but if its content is too high, the anti-crystallization performance of the glass will decrease and the volatility of molten glass will increase. Therefore, the AlF3 content is 0-6%, preferably 0.1%-4.5%, and more preferably 0.5%-3%. In some embodiments, the AlF3 content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, 5.3%, 5.5%, 5.7%, 6%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0056] In some embodiments, by controlling 2×AlF3 / (SrO-ZrO2-Gd2O3-Y2O3-ZnO-Li2O-Na2O-K2O) within the range of 0.02 to 7.00, the Young's modulus of the glass can be increased while the ΔP of the glass can be reduced. g,FTherefore, the preferred value of 2×AlF3 / (SrO-ZrO2-Gd2O3-Y2O3-ZnO-Li2O-Na2O-K2O) is 0.02 to 7.00, more preferably 0.10 to 3.00, and even more preferably 0.20 to 1.00. In some implementations, the value of 2×AlF3 / (SrO-ZrO2-Gd2O3-Y2O3-ZnO-Li2O-Na2O-K2O) can be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.10, 1.20, 1.30, 1. 40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.4 0, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, 5.10, 5.20, 5.30, 5.40, 5.50, 5.60, 5.70, 5.80, 5.90, 6.00, 6.10, 6.20, 6.30, 6.40, 6.50, 6.60, 6.70, 6.80, 6.90, 7.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0057] In some embodiments, by controlling AlF3 / (Al2O3-Gd2O3-Y2O3-K2O-Na2O-P2O5) within the range of 0.01 to 6.00, the abrasion resistance of the glass can be optimized while improving its striation. Therefore, it is preferable that AlF3 / (Al2O3-Gd2O3-Y2O3-K2O-Na2O-P2O5) is 0.01 to 6.00, more preferably 0.05 to 2.50, and even more preferably 0.10 to 1.00. In some implementations, the value of AlF3 / (Al2O3-Gd2O3-Y2O3-K2O-Na2O-P2O5) can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3 70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, 5.10, 5.20, 5.30, 5.40, 5.50, 5.60, 5.70, 5.80, 5.90, 6.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0058] In some embodiments, controlling the 5×AlF3 / La2O3 ratio within the range of 0.02 to 3.00 can improve the hardness of the glass while preventing a deterioration in the Young's modulus. Therefore, it is preferable that the 5×AlF3 / La2O3 ratio is 0.02 to 3.00, more preferably 0.05 to 2.00, and even more preferably 0.10 to 1.00. In some implementations, the value of 5×AlF3 / La2O3 can be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, or 0.67. The values are 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0059] In this invention, by using one or more components selected from Sb₂O₃, SnO₂, and CeO₂ as a clarifying agent containing 0-1%, the clarification effect of the glass can be improved and the bubble content of the glass optimized. Preferably, the content of the clarifying agent is 0-0.5%, more preferably 0-0.2%. In some embodiments, the content of the clarifying agent can be 0, greater than 0, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0060] <Components that should not be present>
[0061] In the glass of this invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo are contained in small amounts, either alone or in combination, the glass will be colored and absorb at specific wavelengths in the visible light region, thereby weakening the property of this invention to improve visible light transmittance. Therefore, it is preferable that the glass does not contain these oxides, especially for optical glass where transmittance in the visible light region is required.
[0062] Oxides of Th, Cd, Tl, Os, Be, and Se have been increasingly subject to controlled use in recent years due to their status as hazardous chemicals. Environmental protection measures are essential not only in glass manufacturing but also in processing and post-product disposal. Therefore, given the importance of environmental impact, it is preferable to avoid the presence of these substances, except where their contamination is unavoidable. As a result, the optical glass becomes virtually free of pollutants. Therefore, the optical glass of this invention can be manufactured, processed, and disposed of even without special environmental countermeasures.
[0063] To achieve environmental friendliness, the optical glass of the present invention preferably does not contain As2O3 and PbO.
[0064] The terms "not containing" and "0" used herein mean that the compound, molecule, or element was not intentionally added to the optical glass of this invention as a raw material; however, as raw materials and / or equipment used in the production of optical glass, there may be certain unintentionally added impurities or components that may be present in small or trace amounts in the final optical glass, and such cases are also within the scope of protection of this patent.
[0065] The performance of the optical glass of the present invention will now be described.
[0066] <Refractive Index and Abbe Number>
[0067] The refractive index (n) of optical glass d ) and Abbe number (ν) d Tested according to the method specified in the national standard GB / T 7962.1—2010.
[0068] In some embodiments, the refractive index (n) of the optical glass of the present invention is... d The lower limit for the refractive index (n) is 1.590, preferably 1.600, and more preferably 1.610. In some embodiments, the refractive index (n) of the optical glass of the present invention is... d The upper limit for the refractive index (n) is 1.660, preferably 1.650, and more preferably 1.640. In some embodiments, the refractive index (n) of the optical glass is... dThe range can be 1.590, 1.593, 1.595, 1.597, 1.600, 1.603, 1.605, 1.607, 1.610, 1.613, 1.615, 1.617, 1.620, 1.623, 1.625, 1.627, 1.630, 1.633, 1.635, 1.637, 1.640, 1.643, 1.645, 1.647, 1.650, 1.653, 1.655, 1.657, 1.660, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0069] In some embodiments, the Abbe number (ν) of the optical glass of the present invention d The lower limit for the Abbe number (ν) is 55.5, preferably 56.0, and more preferably 57.0. In some embodiments, the Abbe number (ν) of the optical glass of the present invention is... d The upper limit for the Abbe number (ν) is 62.5, preferably 61.0, and more preferably 60.0. In some embodiments, the Abbe number (ν) of the optical glass is... d The range can be 55.5, 55.7, 56.0, 56.3, 56.5, 56.7, 57.0, 57.3, 57.5, 57.7, 58.0, 58.3, 58.5, 58.7, 59.0, 59.3, 59.5, 59.7, 60.0, 60.3, 60.5, 60.7, 61.0, 61.3, 61.5, 61.7, 62.0, 62.3, 62.5, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0070] <Coefficient of thermal expansion>
[0071] The coefficient of thermal expansion of optical glass (α) 100℃ / 300℃ Data were tested at 100℃~300℃ according to the method specified in the national standard GB / T7962.16—2010.
[0072] In some embodiments, the coefficient of thermal expansion (α) of the optical glass of the present invention is... 100℃ / 300℃ ) is 90×10 -7 / K or less, preferably 80×10 -7 / K or less, preferably 75×10 -7 / K or below. In some embodiments, the coefficient of thermal expansion of the optical glass (α) is... 100℃ / 300℃ It can be 90×10 -7 / K、89×10 -7 / K、88×10 -7 / K、87×10-7 / K、86×10 -7 / K、85×10 -7 / K、84×10 -7 / K、83×10 -7 / K、82×10 -7 / K、81×10 -7 / K、80×10 -7 / K、79×10 -7 / K、78×10 -7 / K、77×10 -7 / K、76×10 -7 / K、75×10 -7 / K、74×10 -7 / K、73×10 -7 / K、72×10 -7 / K、71×10 -7 / K、70×10 -7 / K、69×10 -7 / K、68×10 -7 / K, etc., and all ranges and subranges between the above values. It should be understood that, in the implementation, any of the above ranges can be combined with any other range.
[0073] <Stability under water resistance>
[0074] Water resistance stability of optical glass (D) W (Powder method) Tested according to the method specified in the national standard GB / T 17129. In this invention, the stability of water resistance can be simply referred to as water resistance.
[0075] In some embodiments, the water resistance stability (D) of the optical glass of the present invention is... W There are two or more categories, with category 1 being preferred.
[0076] <Weather resistance>
[0077] The weather resistance (CR) test method for optical glass is as follows: The glass sample is placed in a test chamber with a relative humidity of 90% and saturated water vapor. The temperature is alternated between 40℃ and 50℃ every hour for 15 cycles. Weather resistance is classified according to the change in turbidity before and after the sample placement. The weather resistance classification is shown in Table 1.
[0078] Table 1.
[0079]
[0080] In some embodiments, the weather resistance (CR) of the optical glass of the present invention is Class 2 or above, preferably Class 1.
[0081] <Density>
[0082] The density (ρ) of optical glass is tested according to the method specified in the national standard GB / T7962.20—2010.
[0083] In some embodiments, the density (ρ) of the optical glass of the present invention is 3.70 g / cm³. 3 The preferred value is 3.60 g / cm³. 3 The following is a preferred value: 3.50 g / cm³ 3 The following is a further preferred value: 3.45 g / cm³ 3 Below. In some embodiments, the density (ρ) of the optical glass can be 3.70 g / cm³. 3 3.69 g / cm 3 3.68g / cm 3 3.67 g / cm 3 3.66 g / cm 3 3.65g / cm 3 3.64 g / cm 3 3.63 g / cm 3 3.62g / cm 3 3.61 g / cm 3 3.60g / cm 3 3.59g / cm 3 3.58g / cm 3 3.57g / cm 3 3.56g / cm 3 3.55g / cm 3 3.54g / cm 3 3.53g / cm 3 3.52g / cm 3 3.51g / cm 3 3.50g / cm 3 3.49 g / cm 3 3.48 g / cm 3 3.47 g / cm 3 3.46 g / cm 3 3.45g / cm 3 3.44 g / cm 3 3.43 g / cm 3 3.42 g / cm 3 3.41 g / cm 3 3.40 g / cm 3 3.39 g / cm 3 3.38g / cm 3 3.37 g / cm3 And so on, as well as all ranges and subranges between the aforementioned values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0084] Knoop Hardness
[0085] Knoop hardness (H) of optical glass K The test was conducted according to the test method specified in the national standard GB / T7962.18-2010. In this invention, Knoop hardness can be simply referred to as hardness.
[0086] In some embodiments, the Knoop hardness (H) of the optical glass of the present invention is... K ) is 520×10 7 Pa or higher, preferably 540 × 10 Pa 7 Pa or higher, more preferably 550 × 10 Pa 7 Pa or higher. In some embodiments, the Knoop hardness (H) of the optical glass is... K (can be 520×10) 7 Pa, 523×10 7 Pa, 525×10 7 Pa, 527×10 7 Pa, 530×10 7 Pa, 533×10 7 Pa, 535×10 7 Pa, 537×10 7 Pa, 540×10 7 Pa, 543×10 7 Pa, 545×10 7 Pa, 547×10 7 Pa, 550×10 7 Pa, 553×10 7 Pa, 555×10 7 Pa, 557×10 7 Pa, 560×10 7 Pa, 563×10 7 Pa, 565×10 7 Pa, 567×10 7 Pa, 570×10 7 Pa, etc., and all ranges and subranges between the aforementioned values. It should be understood that, in the implementation scheme, any of the aforementioned ranges can be combined with any other range.
[0087] <Transition Temperature>
[0088] Transition temperature of optical glass (T) gTest according to the method specified in the national standard GB / T7962.16—2010.
[0089] In some embodiments, the transition temperature (T) of the optical glass of the present invention is... g The temperature range is 610℃ to 680℃ or below, preferably 620℃ to 665℃, and more preferably 630℃ to 655℃. In some embodiments, the transition temperature (T) of the optical glass is... g The values can be 610℃, 613℃, 615℃, 617℃, 620℃, 623℃, 625℃, 627℃, 630℃, 633℃, 635℃, 637℃, 640℃, 643℃, 645℃, 647℃, 650℃, 653℃, 655℃, 657℃, 660℃, 663℃, 665℃, 667℃, 670℃, 673℃, 675℃, 677℃, 680℃, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0090] <wear level>
[0091] Abrasion resistance (F) of optical glass A The wear amount (volume) refers to the ratio of the wear amount of the tested sample to the wear amount (volume) of the standard sample (H-K9 glass) under exactly the same conditions, multiplied by 100. The formula is as follows:
[0092] F A =V / V0×100=(W / ρ) / ( W0 / ρ0)×100
[0093] Where: V—volume wear of the tested sample;
[0094] V0—Standard sample volume wear amount;
[0095] W—Mass wear of the tested sample;
[0096] W0—Standard sample mass wear amount;
[0097] ρ—Density of the sample being measured;
[0098] ρ0 — density of the standard sample.
[0099] In some embodiments, the abrasion degree (F) of the optical glass of the present invention A The lower limit for the wear resistance (F) is 105, preferably 110, and more preferably 116. In some embodiments, the wear resistance (F) of the optical glass of the present invention is... A The upper limit for (F) is 139, preferably 134, and more preferably 128. In some embodiments, the abrasion degree (F) of the optical glass is... AThe range can be 105, 106, 107, 108, 109, 110, 111, 112, 113, 114, 115, 116, 117, 118, 119, 120, 121, 122, 123, 124, 125, 126, 127, 128, 129, 130, 131, 132, 133, 134, 135, 136, 137, 138, 139, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0100] Young's Modulus
[0101] Young's modulus (E) is obtained by ultrasonic testing of its longitudinal and transverse wave velocities, and then calculated using the following formula.
[0102]
[0103] G=V S 2 ρ
[0104] In the formula: E is Young's modulus, Pa;
[0105] G is the shear modulus, Pa;
[0106] V T The transverse wave velocity is in m / s;
[0107] V S The longitudinal wave velocity is given in m / s.
[0108] ρ is the density of glass, in g / cm³ 3 .
[0109] In some embodiments, the Young's modulus (E) of the optical glass of the present invention is 82.0 GPa or higher, preferably 85.0 GPa or higher, and more preferably 87.0 GPa or higher. In some embodiments, the Young's modulus (E) of the optical glass can be 82.0 GPa, 82.3 GPa, 82.5 GPa, 82.7 GPa, 83.0 GPa, 83.3 GPa, 83.5 GPa, 83.7 GPa, 84.0 GPa, 84.3 GPa, 84.5 GPa, 84.7 GPa, 85.0 GPa, 85.3 GPa, 85.5 GPa, 85.7 GPa, etc. 6.0 GPa, 86.3 GPa, 86.5 GPa, 86.7 GPa, 87.0 GPa, 87.3 GPa, 87.5 GPa, 87.7 GPa, 88.0 GPa, 88.3 GPa, 88.5 GPa, 88.7 GPa, 89.0 GPa, 89.3 GPa, 89.5 GPa, 89.7 GPa, 90.0 GPa, and all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0110] <Effervescence>
[0111] The bubble degree of optical glass is tested according to the method specified in the national standard GB / T7962.8—2010.
[0112] In some embodiments, the bubble degree of the optical glass of the present invention is grade A or above, preferably grade A0 or above, and more preferably grade A. 00 class.
[0113] <Stripe>
[0114] The method for testing the stripe density of optical glass is as follows: A stripe meter is composed of a point light source and a lens. The stripes are compared with the standard sample from the direction in which they are most easily visible, and the sample is divided into four levels according to Table 2.
[0115] Table 2. Rhombus Grading Standards
[0116]
[0117] In some embodiments, the striation of the optical glass of the present invention is grade C or above, preferably grade B or above.
[0118] <Relative Partial Dispersion Deviation Value>
[0119] The following formula illustrates the relative partial dispersion (P) g,F ) and relative partial dispersion deviation (ΔP) g,F ) origin:
[0120] The relative partial dispersion of wavelengths x and y is expressed by the following equation (1):
[0121] P x,y =(n x -n y ) / (n F -n C (1)
[0122] According to the Abbe number formula, for most so-called "normal glass" (hereinafter, H-K6 and F4 are selected as "normal glass"), the following equation (2) holds true.
[0123] P x,y =m x,y •v d +b x,y (2)
[0124] This linear relationship is based on P. x,y For the ordinate, v d The x-axis is used to represent the coordinates, where m is the x-axis. x,y Let b be the slope. x,y This is the intercept.
[0125] As is well known, the correction of a second-order spectrum, that is, the achromatic correction of more than two wavelengths, requires at least one type of glass that does not conform to the above formula (2) (i.e., its P). x,y The value deviates from Abbe's empirical formula, and the deviation is expressed as ΔP. x,y This means that each P x,y -v d The point is translated by ΔP relative to the "normal line" that conforms to equation (2) above. x,y Quantity, thus the ΔP of each glass x,y The numerical value can be obtained using the following formula (3):
[0126] P x,y =m x,y •v d +b x,y +ΔP x,y (3)
[0127] Therefore, ΔP x,y It quantitatively represents the deviation of the special dispersion characteristics compared to "normal glass".
[0128] Therefore, from the above, we can obtain the relative partial dispersion (P). g,F ) and relative partial dispersion deviation (ΔP) g,F The calculation formulas for ) are as follows: (4) and (5):
[0129] P g,F =(n g -n F ) / (n F -n C (4)
[0130] ΔP g,F =P g,F -0.6457 +0.001703v d (5)
[0131] In some embodiments, the relative partial dispersion deviation (ΔP) of the optical glass of the present invention g,F The relative partial dispersion deviation (ΔP) of the optical glass is -0.0010 or less, preferably -0.0020 or less, and more preferably -0.0035 or less. In some embodiments, the relative partial dispersion deviation (ΔP) of the optical glass is... g,F The range can be -0.0010, -0.0013, -0.0015, -0.0017, -0.0020, -0.0023, -0.0025, -0.0027, -0.0030, -0.0033, -0.0035, -0.0037, -0.0040, -0.0043, -0.0045, -0.0047, -0.0050, -0.0053, -0.0055, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0132] <400nm light transmittance>
[0133] 400nm light transmittance of optical glass (τ) 400nm The test was conducted according to the method specified in GB / T 7962.12-2010, and the thickness of the test sample was 10mm ± 1mm.
[0134] In some embodiments, the 400nm light transmittance (τ) of the optical glass of the present invention 400nm The transmittance (τ) of the optical glass is 98.0% or higher, preferably 99.0% or higher, and more preferably 99.5% or higher. In some embodiments, the transmittance (τ) of the optical glass at 400 nm is... 400nm The values can be 98.0%, 98.1%, 98.2%, 98.3%, 98.4%, 98.5%, 98.6%, 98.7%, 98.8%, 98.9%, 99.0%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0135] [Manufacturing methods for optical glass]
[0136] The manufacturing method of the optical glass of this invention is as follows: The glass of this invention is produced using conventional raw materials and processes, including but not limited to oxides, hydroxides, fluorides, various salts (carbonates, nitrates, sulfates, phosphates, metaphosphates), boric acid, etc., as raw materials. After being prepared according to conventional methods, the prepared furnace charge is put into a melting furnace (such as a platinum or platinum alloy crucible) at 1000℃~1400℃ for melting. After clarification and homogenization, a homogeneous molten glass free of undissolved substances is obtained. This molten glass is then cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods, and process parameters according to actual needs.
[0137] [Glass preforms and optical components]
[0138] Glass preforms can be manufactured from the produced optical glass using methods such as direct drop forming, grinding, or hot pressing. Specifically, glass preforms can be manufactured by directly and precisely drop-forming molten optical glass into precision glass preforms, or by machining such as grinding and polishing, or by hot pressing a preform made from optical glass for compression molding followed by grinding. It should be noted that the methods for preparing glass preforms are not limited to the methods described above.
[0139] As described above, the optical glass of the present invention is useful for various optical components and optical designs. It is particularly preferred to form a preform from the optical glass of the present invention, and to use the preform for hot pressing, precision stamping, etc., to manufacture optical components such as lenses and prisms.
[0140] The optical glass of this invention can be used to draw optical components such as optical fibers, that is, the optical components described in this invention also include optical fibers.
[0141] Both the glass preform and the optical element of the present invention are formed from the optical glass described above. The glass preform of the present invention possesses the excellent properties of optical glass; the optical element of the present invention possesses the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.
[0142] Examples of lenses include concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, plano-concave lenses, and so on, where the lens surface is spherical or aspherical.
[0143] [Optical Instruments]
[0144] The optical glass of this invention, or the optical elements formed by the optical glass, can be used to manufacture optical instruments such as photographic equipment, video equipment, endoscopes, projection equipment, display equipment, vehicle-mounted equipment, monitoring equipment, AR (augmented reality) equipment, MR (mixed reality) equipment, VR (virtual reality) equipment, and mobile electronic devices (such as mobile phones, watches, etc.).
[0145] Example
[0146] <Example of Optical Glass>
[0147] To further illustrate and explain the technical solution of the present invention, the following non-limiting embodiments are provided.
[0148] In this embodiment, optical glass with the composition shown in Tables 3 to 5 was obtained by using the above-described optical glass manufacturing method, and the performance of each glass was measured by the test method described in this invention. The measurement results are shown in Tables 3 to 5.
[0149] Table 3.
[0150]
[0151]
[0152] Table 4.
[0153]
[0154]
[0155]
[0156] Table 5.
[0157]
[0158]
[0159] <Example of Glass Prefabricated Components>
[0160] The glass obtained from optical glass examples 1# to 15# is used to manufacture preforms of various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses, by means of grinding, hot pressing, precision stamping, or other molding methods.
[0161] <Optical Component Examples>
[0162] Annealing these preforms obtained from the above glass preform examples reduces internal stress in the glass while fine-tuning the refractive index, so that optical properties such as the refractive index reach the desired values.
[0163] Next, the prefabricated parts are ground and polished to produce various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. Anti-reflective coatings can also be applied to the surface of the resulting optical elements.
[0164] The optical glass of this invention is drawn into optical components such as optical fibers using conventional techniques in the art.
[0165] <Examples of Optical Instruments>
[0166] The optical elements obtained from the above-described optical element embodiments are optically designed and formed into optical components or assemblies by using one or more optical elements, and then assembled in various optical instruments. They can be used in, for example, imaging devices, monitoring devices, endoscopes, sensors, microscopes, medical technology, digital projection, communication, optical communication technology / information transmission, optics / lighting in the automotive field, photolithography, excimer lasers, wafers, computer chips, as well as integrated circuits and electronic devices including such circuits and chips, mobile phones, etc.
[0167] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0168] The embodiments described above are merely illustrative of several implementation methods of this application, intended to facilitate a detailed understanding of the technical solutions of this application, but should not be construed as limiting the scope of protection of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the scope of protection of this application. It should be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the scope of protection of the appended claims. Therefore, the scope of protection of this patent application should be determined by the content of the appended claims, and the specification can be used to interpret the content of the claims.
Claims
1. Optical glass, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 18%–33%; B2O3: 18%–33%; SrO: 3%–15%; BaO: 13%–26%; La2O3: 9%–23%; ZrO2: 0.1%–9%; Al2O3: 0.1%–9%, of which the SrO / ZrO2 ratio is 1.00–8.
00.
2. The optical glass according to claim 1, characterized in that, Its components, expressed as a weight percentage, also contain: MgO: 0–4.5%; and / or CaO: 0–4.5%; and / or ZnO: 0–4.5%; and / or Gd₂O₃: 0–4.5%; and / or Y₂O₃: 0–4.5%; and / or Yb₂O₃: 0–4.5%; and / or AlF₃: 0–6%; and / or Li₂O: 0–4.5%; and / or Na₂O: 0–4.5%; and / or K₂O: 0–4.5%; and / or Nb₂O₅: 0–3%; and / or TiO₂: 0–3%; and / or WO₃: 0–3%; and / or Ta₂O₅: 0–3%; and / or P₂O₅: 0–3%; and / or clarifying agent: 0–1%, wherein the clarifying agent is one or more of Sb₂O₃, SnO₂, and CeO₂.
3. Optical glass, characterized in that, Its composition includes SiO2, B2O3, SrO, BaO, La2O3, ZrO2, and Al2O3, expressed as a weight percentage, with SrO / ZrO2 ratio ranging from 1.00 to 8.
00. The refractive index n of the optical glass is... d The Abbe number ν ranges from 1.590 to 1.
660. d Its strength ranges from 55.5 to 62.5, and its Knoop hardness is 520 × 10⁻⁶. 7 Above Pa, the relative partial dispersion deviation ΔP g,F It is below -0.0010.
4. The optical glass according to claim 3, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 18%–33%; and / or B2O3: 18%–33%; and / or SrO: 3%–15%; and / or BaO: 13%–26%; and / or La2O3: 9%–23%; and / or ZrO2: 0.1%–9%; and / or Al2O3: 0.1%–9%; and / or MgO: 0–4.5%; and / or CaO: 0–4.5%; and / or ZnO: 0–4.5%; and / or Gd2O3: 0–4.5%; and / or Y2O3. : 0-4.5%; and / or Yb2O3: 0-4.5%; and / or AlF3: 0-6%; and / or Li2O: 0-4.5%; and / or Na2O: 0-4.5%; and / or K2O: 0-4.5%; and / or Nb2O5: 0-3%; and / or TiO2: 0-3%; and / or WO3: 0-3%; and / or Ta2O5: 0-3%; and / or P2O5: 0-3%; and / or clarifying agent: 0-1%, wherein the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.
5. The optical glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as weight percentages, wherein: SrO / ZrO2 is 1.40–6.00, preferably 1.70–3.00; and / or (La2O3+SrO) / SiO2 is 0.50–2.00, preferably 0.60–1.60, more preferably 0.75–1.20; and / or 2×AlF3 / (SrO-ZrO2-Gd2O3-Y2O3-ZnO-Li2O-Na2O-K2O) is 0.02–7%. 0.00, preferably 2×AlF3 / (SrO-ZrO2-Gd2O3-Y2O3-ZnO-Li2O-Na2O-K2O) is 0.10 to 3.00, more preferably 2×AlF3 / (SrO-ZrO2-Gd2O3-Y2O3-ZnO-Li2O-Na2O-K2O) is 0.20 to 1.00; and / or 5×AlF3 / La2O3 is 0.02 to 3.00, preferably 5×AlF3 / La2O3 is 0.05 to 2.00, more preferably 5×AlF3 / La2O3 is 0.10 to 1.
00.
6. The optical glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as weight percentages, wherein: (La2O3+Gd2O3+Y2O3+CaO) / SrO is 0.80 to 4.50, preferably (La2O3+Gd2O3+Y2O3+CaO) / SrO is 1.20 to 3.50, more preferably (La2O3+Gd2O3+Y2O3+CaO) / SrO is 1.60 to 2.50; and / or (TiO2+Nb2O5+WO3+Ta2O5) / SrO is 0.80 or less, preferably (TiO2+Nb2O5+WO3+Ta2O5) / SrO is 0.50 or less, more preferably (TiO2+Nb2O5+WO3+Ta2O5) / SrO The ratio is preferably 0.30 or less, and more preferably (TiO2+Nb2O5+WO3+Ta2O5) / SrO is 0.10 or less; and / or (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) / SrO is 1.00 or less, preferably (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) / SrO is 0.70 or less, and more preferably (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) / SrO is 0. The ratio of (Li2O+Na2O+K2O+Gd2O3+Y2O3+ZnO+CaO+MgO+TiO2+Nb2O5) / SrO is preferably 0.10 or less; and / or the ratio of (La2O3+SrO+BaO) / B2O3 is 1.00 to 2.60, preferably (La2O3+SrO+BaO) / B2O3 is 1.30 to 2.30, more preferably (La2O3+SrO+BaO) / B2O3 is 1.50 to 2.00; and / or the ratio of (La2O3+Gd2O3+Y2O3+Yb2O3+ZnO) / BaO is 0.40 to 2.00, preferably (La2O3+Gd2O3+... The ratio of (Y2O3+Yb2O3+ZnO) / BaO is 0.50 to 1.50, more preferably (La2O3+Gd2O3+Y2O3+Yb2O3+ZnO) / BaO is 0.60 to 1.20; and / or (SiO2+BaO+CaO+MgO+ZrO2+Gd2O3+Y2O3) / B2O3 is 1.00 to 3.20, more preferably (SiO2+BaO+CaO+MgO+ZrO2+Gd2O3+Y2O3) / B2O3 is 1.30 to 2.80, more preferably (SiO2+BaO+CaO+MgO+ZrO2+Gd2O3+Y2O3) / B2O3 is 1.60 to 2.
20.
7. The optical glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as weight percentages, wherein: BaO / (ZrO2+Al2O3) is 1.00 to 8.00, preferably BaO / (ZrO2+Al2O3) is 1.50 to 5.50, more preferably BaO / (ZrO2+Al2O3) is 2.30 to 3.50; and / or (Li2O+Na2O+K2O+MgO+CaO+ZnO) / (ZrO2+Al2O3) is 1.00 or less, preferably (Li2O+Na2O+K2O+MgO+CaO+ZnO) / (ZrO2+Al2O3) is 0.70 or less, more preferably (Li2O+Na2O+K2O+MgO+CaO+ZnO) / (ZrO2+Al2O3) is 0.40 or less, and even more preferably (Li2O+Na2O+K2O+MgO+CaO+ZnO) / ( The ratio of ZrO2+Al2O3 is 0.01 to 0.15; and / or the ratio of (Gd2O3+Y2O3) / ZrO2 is 1.00 or less, preferably (Gd2O3+Y2O3) / ZrO2 is 0.70 or less, more preferably (Gd2O3+Y2O3) / ZrO2 is 0.50 or less, and even more preferably (Gd2O3+Y2O3) / ZrO2 is 0.20 or less; and / or AlF3 / The ratio of AlF3 / (Al2O3-Gd2O3-Y2O3-K2O-Na2O-P2O5) is 0.01 to 6.00, preferably 0.05 to 2.50, and more preferably 0.10 to 1.
00.
8. The optical glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as weight percentages, wherein: SiO2: 21%–30%, preferably SiO2: 23%–27%; and / or B2O3: 21%–30%, preferably B2O3: 23%–27%; and / or SrO: 5%–12%, preferably SrO: 6%–10.5%; and / or BaO: 15%–24%, preferably BaO: 17%–22%; and / or La2O3: 11%–19.5%, preferably La2O3: 13%–18%; and / or ZrO2: 1%–7%, preferably ZrO2: 2%–5.5%; and / or Al2O3: 1%–7%, preferably ZrO2: 2%–5.5%; and / or Al2O3: 1%–7%; and / or SrO2: 1%–7%; preferably ZrO2: 2%–5.5%; and / or SrO2: 1%–7%; preferably SrO2: 1%–2%; and / or SrO2: 1%–2 ... 3: 1%–7%, preferably Al2O3: 2.5%–6%; and / or MgO: 0–3%, preferably MgO: 0–1%, more preferably MgO-free; and / or CaO: 0–3%, preferably CaO: 0–1%, more preferably CaO-free; and / or ZnO: 0–2%, preferably ZnO: 0–0.5%, more preferably ZnO-free; and / or Gd2O3: 0–3%, preferably Gd2O3: 0–0.5%, more preferably Gd2O3-free; and / or Y2O3: 0–3%, preferably Y2O3: 0–0.5%, more preferably Y2O3-free. And / or Yb2O3: 0-3%, preferably Yb2O3: 0-1%, more preferably without Yb2O3; and / or AlF3: 0.1%-4.5%, preferably AlF3: 0.5%-3%; and / or Li2O: 0-3%, preferably Li2O: 0-1%; and / or Na2O: 0-3%, preferably Na2O: 0-1%, more preferably without Na2O; and / or K2O: 0-3%, preferably K2O: 0-1%, more preferably without K2O; and / or Nb2O5: 0-2%, preferably Nb2O5: 0-1%, more preferably without Nb2O. O5; and / or TiO2: 0-2%, preferably TiO2: 0-1%, more preferably without TiO2; and / or WO3: 0-2%, preferably WO3: 0-1%, more preferably without WO3; and / or Ta2O5: 0-2%, preferably Ta2O5: 0-1%, more preferably without Ta2O5; and / or P2O5: 0-2%, preferably P2O5: 0-1%, more preferably without P2O5; and / or clarifying agent: 0-0.5%, preferably clarifying agent: 0-0.2%, wherein the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.
9. The optical glass according to any one of claims 1 to 4, characterized in that, The refractive index n of the optical glass d The Knoop hardness is 1.590–1.660, preferably 1.600–1.650, more preferably 1.610–1.640; and / or the Knoop hardness is 520 × 10⁻⁶. 7 Pa or higher, preferably 540 × 10 Pa 7 Pa or higher, more preferably 550 × 10 Pa 7 Pa or above; and / or relative partial dispersion deviation ΔP g,F The value is -0.0010 or less, preferably -0.0020 or less, more preferably -0.0035 or less; and / or the Abbe number ν d The coefficient of thermal expansion is 55.5–62.5, preferably 56.0–61.0, more preferably 57.0–60.0; and / or the coefficient of thermal expansion α. 100℃ / 300℃ 90×10 -7 / K or less, preferably 80×10 -7 / K or less, preferably 75×10 -7 / K or below; and / or 400nm light transmittance τ 400nm The purity is 98.0% or higher, preferably 99.0% or higher, more preferably 99.5% or higher; and / or the water resistance stability is Class 2 or higher, preferably Class 1; and / or the weather resistance is Class 2 or higher, preferably Class 1; and / or the density is 3.70 g / cm³. 3 The preferred value is 3.60 g / cm³. 3 The following is a preferred value: 3.50 g / cm³ 3 The following is a further preferred value: 3.45 g / cm³ 3 The following are also considered: a transition temperature of 610°C to 680°C, preferably 620°C to 665°C, more preferably 630°C to 655°C; a wear degree of 105 to 139, preferably 110 to 134, more preferably 116 to 128; a Young's modulus of 82.0 GPa or higher, preferably 85.0 GPa or higher, more preferably 87.0 GPa or higher; and / or a bubble degree of A grade or higher, preferably A0 grade or higher, more preferably A. 00 Grade; and / or stripe density of grade C or above, preferably grade B or above.
10. A glass preform, characterized in that, It is made of the optical glass described in any one of claims 1 to 9.
11. An optical element, characterized in that, It is made of the optical glass described in any one of claims 1 to 9, or of the glass preform described in claim 10.
12. An optical instrument, characterized in that, It contains the optical glass according to any one of claims 1 to 9, and / or contains the optical element according to claim 11.